Health Promotion in Schools through Educational Activities - Yadav, Saroj (JOURNAL OF INDIAN EDUCATION, 2013)
Education is the key to awareness generation among people about various issues including health. The most crucial role that education, particularly school education, is expected to play in this context is to provide information and develop positive attitude among learners towards health related issues and influence their value orientation in respect of these issues so that they take informed and rational decisions for observing better quality of life. In this context, school education, especially Health and Physical Education occupies a central position by making students not only aware–but also in attitude formation and skill development among learners towards holistic health including reproductive and sexual health. Given the multidimensional nature of health, many opportunities for cross–curricular learning are provided through subjects like sciences, social sciences, and activities such as National Service Scheme, Bharat Scouts and Guides and various programmes like National Population Education Project (NPEP,) Adolescence Education Programme (AEP), and Comprehensive School Health Programme (CSHP).